Quantifying Antimicrobial Exposure: Hazards in Populations With End-Stage Renal Disease. (5th December 2016) - Snyder, Graham M.; McCoy, Christopher; D'Agata, Erika M. C.
Abstract : Using a rigorously collected data set of antimicrobial use among patients receiving chronic hemodialysis, antimicrobial use was calculated using 3 different methodologies: daily defined dose, days of therapy, and start–stop days. Estimates of antimicrobial use varied by as much as 10-fold, depending on the type of antimicrobial. Infect Control Hosp Epidemiol 2017;38:360–363